Judges of the Supreme Court of India, 1950-1989 - Gadbois, George H. (George Harold), 1936- (New Delhi ; Oxford : Oxford University Press, 2011)
This book presents biographies of the first ninety-three judges who served the Supreme Court of India from 1950 to 1989. The essays are based on author's interviews with the judges and their family and friends. They provide an engaging account of the first forty years of the Supreme Court of India.
Includes bibliographical references and index.
Description based on print version record.
Keywords: India. -- Supreme Court; Judges -- India -- Registers; Judges -- India -- Biography